Socio-Economic Impacts by the Internet Usage of Teenagers in Villages - Ekasari, Putri; Hadi Dharmawan, Arya (Sodality: Jurnal Sosiologi Pedesaan, 2012)
The study was done in two village, they are Cibatok I Village and Pangradin Village, The Bogor District of West Java, Indonesia.The purposes of this study were 1) to analyse and determine the impacts of the use of internet in teenagers characteristics to internet usage pattern in two villages 2) to analyze the socio-economic impact brought by internet usage pattern of teenagers in two villages.This study was approached by using quantitative method supported by qualitative method. Data obtained through observation, depth interviews and interviews using questionnaires. Meanwhile, the results of this study showed 1) The differences of internet usage pattern in the two villages 2) The availability of internet access in Cibatok I Village have made impacts to the socio-economic changes of teenagers life. Meanwhile, it is not clearly seen in teenagers live at Pangradin Village